Pengembangan Media Toponimi Desa-Desa Berbasis Google Sites Pada pembelajaran IPS Untuk Penguatan Literasi Budaya dan Kewargaan - I Putu Eka Arimbawa; I Wayan Kertih; Tuty Maryati (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2026)
The contextual approach plays a strategic role in Social Studies (IPS) learning by connecting theoretical concepts with students’ everyday life experiences. The Merdeka Curriculum emphasizes the development of critical thinking skills, the ability to solve social problems, and an understanding of cultural diversity and social interaction dynamics within the surrounding environment. However, the utilization of village toponymy as a learning resource in schools remains suboptimal, as many teachers still rely on conventional textbooks.Therefore, this study aims to develop Google Sites–based village toponymy learning media that are valid and practical, and to examine their effectiveness in improving the cultural and civic literacy of seventh-grade junior high school students. This research was conducted at SMP Negeri 3 Negara using a Research and Development (R&D) method with the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate).The data analysis techniques included qualitative, quantitative, statistical, and inferential statistical analyses. The results showed that the material expert validation reached 93.56%, the media expert validation reached 94.45%, and the practicality assessment reached 92.50%. These results indicate that the Google Sites–based Village Toponymy Media of Jembrana Regency is categorized as “very good” and is both valid and practical for use in seventh-grade Social Studies learning.Furthermore, students’ average scores increased from 61.20 to 82.40. The results of the Paired Samples t-test using SPSS 25 showed that t_calculated = 36.733 > t_table = 2.0638, with a significance value (2-tailed) of 0.000 < 0.05. These findings demonstrate that the developed learning media are effective in improving students’ cultural and civic literacy in seventh-grade Social Studies learning